Development of Student Worksheets Based on Discovery Learning to Improve Students’ Critical Thinking Skills - Ainun Mardiah; Zaini Dahlan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop a Discovery Learning-based Student Worksheets (LKPD) that is feasible, practical, and effective to improve students’ critical thinking skills. This research is classified as development research using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade students at MIS Maura El-Mumtaz, Binjai City, North Sumatra, totaling 21 students. Based on the results of the study in terms of feasibility, the material expert obtained a score of 98% categorized as feasible, and the media expert obtained a score of 95% categorized as feasible. In terms of practicality, the results from the educators’ responses showed an average score of 94% classified as very practical, and the results from the teachers’ responses showed a score of 96% categorized as very practical. In terms of effectiveness, the Student Worksheets were tested through a pretest and posttest using critical thinking indicators. The average pretest score was 7.86, while the average posttest score was 19.50. The average n-gain score obtained was 0.94, categorized as very effective. Thus, the Discovery Learning-based Student Worksheets developed are feasible, practical, and effective for use in science learning at the elementary school level to improve students’ critical thinking skills